Insights into the Planetary Dynamics of Hd 206893 with Alma - Perez-Marquez, S (Oxford University Press, 2020)
Radial substructure in the form of rings and gaps has been shown to be ubiquitous among protoplanetary discs. This could be the case in exo-Kuiper belts as well, and evidence for this is emerging. In this paper, we present ALMA observations of the debris/planetesimal disc surrounding HD 206893, a system that also hosts two massive companions at 2 and 11 au. Our observations reveal a disc extending from 30 to 180 au, split by a 27 au wide gap centred at 74 au, and no dust surrounding the reddened brown dwarf (BD) at 11 au. The gap width suggests the presence of a 0.9MJup planet at 74 au, which would be the third companion in this system. Using previous astrometry of the BD, combined with our derived disc orientation as a prior, we were able to better constrain its orbit finding it is likely eccentric (0.14+−000504). For the innermost companion, we used radial velocity, proper motion anomaly, and stability considerations to show its mass and semimajor axis are likely in the ranges 4-100MJup and 1.4-4.5 au. These three companions will interact on secular time-scales and perturb the orbits of planetesimals, stirring the disc and potentially truncating it to its current extent via secular resonances. Finally, the presence of a gap in this system adds to the growing evidence that gaps could be common in wide exo-Kuiper belts. Out of six wide debris discs observed with ALMA with enough resolution, four to five show radial substructure in the form of gaps. © 2020 The Author(s)
Keywords: methods: numerical; techniques: interferometric; planets and satellites: dynamical evolution and stability; circumstellar matter; stars: individual: HD 206893; submillimetre: planetary systems